2017
DOI: 10.15520/ijnd.2017.vol7.iss6.229.26-33
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Nursing Informatics Competency and Nurses’ Attitude toward Evidence-Based Practice among Qualified Nurses at Mansoura Oncology Center

Abstract: Nowadays, Nursing informatics and evidence based practice (EBP) are considered an important practices in the success of patient care in any organization. Accordingly, nurses, have to establish informatics experience to effectively implement evidence based practice. The aim of this study was to assess the relation between nursing informatics competency and nurses' attitude toward evidence-based practice among qualified nurses at Mansoura Oncology center. Design of the study descriptive correlation study was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
3
20
2
1
Order By: Relevance
“…Contrary to our findings, other studies indicated that nurses' IT competency was within the range of no-low level of competency [26,43,44]. Some other studies reported the nurses' IT competency at the expert and proficient levels [11,45,46]. Probably the high level of IT competency in these participants is existence of a nursing informatics' course in their curriculum and difference in their educational degree.…”
Section: Principal Findingscontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, other studies indicated that nurses' IT competency was within the range of no-low level of competency [26,43,44]. Some other studies reported the nurses' IT competency at the expert and proficient levels [11,45,46]. Probably the high level of IT competency in these participants is existence of a nursing informatics' course in their curriculum and difference in their educational degree.…”
Section: Principal Findingscontrasting
confidence: 99%
“…In line with these developments, nurses must embrace innovation and use their abilities and knowledge to change and develop their old ways of thinking [10]. They are also required to actively participate in designing and deploying IT in health care [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies indicated that nurses' NI competency was low [14,38,39]. Some other studies reported the nurses' NI competency at the expert and pro cient levels [2,40,41].…”
Section: Discussionmentioning
confidence: 98%
“…HIT plays an important role in nursing practice, and nurses have participated in the conception, design and implementation of HIT. Following the development of information technology initiatives in nursing, the nursing informatics (NI) discipline has been emerged due to the expansion of the knowledge required in this eld [2]. NI is a specialty that integrates nursing science, computer science, and information science to manage and communicate data, information, and knowledge in nursing practice [3,4].…”
Section: Introductionmentioning
confidence: 99%